2022
DOI: 10.24141/2/6/1/4
|View full text |Cite
|
Sign up to set email alerts
|

The Knowledge and Photoprotective Behaviour of the Hungarian Population in Relation to Skin Cancer

Abstract: Introduction. The carcinogenic ultraviolet range of sunlight plays a major role in the development of malignant skin tumours with a steadily increasing incidence. It shows a significant upward trend in our country, with 2,742 new cases registered in 2016, nearly 15% of which were under 40 years of age. With conscious behaviour and the use of sunscreen products, the incidence of skin tumours can be reduced. The aim of the study is to assess the Hungarian population’s knowledge about skin cancer and attitudes to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Similarly, Mousavi et al's findings revealed that older adults had a low level of knowledge about skin cancer [ 34 ]. Of note, multiple studies have shown no significant relationship between age and KAP toward skin cancer [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Mousavi et al's findings revealed that older adults had a low level of knowledge about skin cancer [ 34 ]. Of note, multiple studies have shown no significant relationship between age and KAP toward skin cancer [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%